Pengaruh Permainan Tradisional Tupai Pemburu Terhadap Kecepatan Lari Sprint - Helvina, Nadia; Mori Saputra, Deka Ismi; Wulandari, Titis; Aprizan (Jurnal Muara Olahraga, 2024)
Traditional games are a symbol of knowledge that has been passed down from generation to generation and have various functions or messages behind them, where in principle the games can be played by anyone who is interested, both children and adults. This research aims to determine the effect of the traditional game of squirrel hunter on the sprint speed of extracurricular students at SMPN Muara Bungo. This study is an experimental study with a one-group pretest-posttest design with a population of 25 students. The sampling technique was purposive sampling of 15 students. The study was conducted in the field of SMPN 3 Muara Bungo and the MTQ Sarunai Baru track, carried out for 16 meetings, in the form of a sprint speed test. The data analysis technique used in this study was the normality, homogenitas, and hypothesis test using SPSS 22. Based on the research results, it was found that there was an influence of the traditional squirrel hunter game on sprint running. If ρ <0.05 then Ha is accepted and H0 is rejected. Based on the results of the t-test analysis of sprint running speed in extracurricular students of SMPN 3 Muara Bungo with the traditional squirrel hunter game, the value of ρ (0.000) <0.05 showed that there was an influence of the traditional squirrel hunter game on sprint running speed. While the t-test value (9.865) .<ttable (2.144). from the results of the t-test value, it can be explained that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, meaning that the results show that there is a significant influence in the traditional squirrel hunter game on sprint running speed.